STRATEGI PENGEMBANGAN EKOWISATA BERBASIS PENYU HIJAU DI KAWASAN PANTAI SUKAMADE TAMAN NASIONAL MERU BETIRI - Dylla Axaraliefya; Nina Herlina; Toto Supartono (Faculty of Forestry and Environment, Universitas Kuningan, 2023)
The Sukamade Beach area of Meru Betiri National Park is one of the distribution areas for green turtles in Indonesia. The existence of these green turtles has the potential to become an ecotourism attraction. The aim of this research is to determine the potential of green turtles (nesting season and nesting behavior) and to develop green turtle-based ecotourism for Meru Betiri National Park Management. The research method used for data collection is the